PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENINGKATKAN PERLINDUNGAN KEMANUSIAAN PADA KONFLIK ROHINGYA DI MYANMAR - Neirata, Indyra Auliya; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The humanitarian crisis in Rakhine State, Myanmar, stems from long-standing structural discrimination, military violence, and mass displacement of the Rohingya ethnic group. In the absence of adequate state protection, the International Committee of the Red Cross (ICRC) emerges as a key non-state actor providing essential humanitarian assistance and protection. Using pluralist perspectives and Humanitarian Diplomacy Theory, this study examines how the ICRC fulfills its mandate through negotiation, neutrality, and direct engagement in conflict-affected areas. The findings demonstrate that the ICRC contributes through various programs under the Protection and Assistance Programs, including Water and Habitat, Emergency Relief, Health Assistance, civilian protection, and detention visits. Despite restricted access and unstable security conditions, the ICRC consistently upholds its humanitarian principles. Although it does not resolve the root causes of the conflict, the organization effectively mitigates humanitarian suffering and improves access to basic rights for the remaining Rohingya population in Myanmar. Keywords: ICRC, humanitarian diplomacy, Myanmar conflict.